HOUSEHOLD WATER AND WASTE MANAGEMENT OF COMMUNITIES NEAR SPRING WATERS IN ARGAO, CEBU - Alburo, Rosalyn P.; Alburo, Hemres M.; Cutillas, A L (Journal of Agriculture and Technology Management, 2018)
This study recognized the importance of water in life. As such, 241 households from 25 spring water communities in Argao, Cebu were interviewed. The interview looked into the utilization of spring waters, waste generation and disposal, as well as, their perceptions on water and  waste  management.  Results  showed  that  households  used  spring  waters  for  drinking, cooking, washing and bathing. Eight (8) springs have existing piping system that transports water to other sitios. Nine (9) springs support rice farms. Kitchen waste, glass bottles, paper, garden waste (lawn trimmings), plastic bags, broken glasses, hard plastics, cartons/boxes, metals and pet wastes, comprised the top 10 wastes generated by households and the disposal varies with waste types. It was noted that the respondents’ perceptions were significantly correlated with the level of education. Moreover, analyses showed that the respondents’ belief were in conflict with their practices.